The modern researches of the interdependence between traditional physical culture of China and ancient Chinese philosophy - Zhengwei, Fang (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The main directions of the interpretation of the interdependence between the sports practices and the philosophical heritage of China’s traditional have been examinated. In this regard China’s traditional physical culture is interpreted as an organic part of the ancient Chinese cultural continuum that on the different step of development reflected special values, views, customs and laws of traditional society ancient China. Interaction between sports practices and the development of China’s traditional philosophy in the scientific literature appears in different interpretations, which are also explored in the article taking into account the geographical differences in Chinese traditional culture.